Odpowiedź :
g)
[tex] - 3 \frac{2}{3} + 1 \frac{1}{6} = - \frac{11}{3} + \frac{7}{6} = - \frac{22}{6} + \frac{7}{6} = - \frac{15}{6} = - \frac{5}{3} = - 1 \frac{2}{3} [/tex]
h)
[tex] - 2 \frac{3}{5} - 1 \frac{14}{15} = - \frac{13}{5} - \frac{29}{15} = - \frac{39}{15} - \frac{29}{15} = - \frac{68}{15} = - 4 \frac{8}{15} [/tex]
i)
[tex] - 2 \frac{3}{5} + 1 \frac{14}{15} = - \frac{13}{5} + \frac{29}{15} = - \frac{39}{15} + \frac{29}{15} = - \frac{10}{15} = - \frac{2}{3} [/tex]
j)
[tex]1 \frac{6}{8} - \frac{3}{8} = \frac{14}{8} - \frac{3}{8} = \frac{11}{8} [/tex]
k)
[tex] - 4 \frac{1}{2} - \frac{4}{6} = - \frac{9}{2} - \frac{4}{6} = - \frac{27}{6} - \frac{4}{6} = - \frac{31}{6} = - 5 \frac{1}{6} [/tex]